Drawing birds - Forkner, Andrew (Turnbridge Wells, Kent Search Press, 2018)
This book is an expert guide to producing beautiful lifelike drawings of birds in their natural habitat. Artists of all interests will find a lot to inspire them in this detailed, practical and beautiful guide on drawing birds. The book includes sections on materials, basic techniques and reference gathering, as well as how to draw the key features of birds such as beaks, eyes, claws, wings and feathers. A specia
1
Keywords: Birds in art; Drawing -- Technique